2022
DOI: 10.3389/fpsyg.2022.929841
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of EFL Teachers’ Hope and Trust on Their Academic Grit: A Theoretical Review

Abstract: The role of emotions in second/foreign language education has been exponentially highlighted in the literature. However, the interplay of English as a foreign language (EFL) teachers’ hope, trust, and grit has witness a scant attention among L2 researchers. Against this shortcoming, the present mini-review article made an effort to offer a theoretical analysis of the theoretical and empirical underpinnings of these three constructs. In so doing, it presented the definitions, conceptualizations, dimensions, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Teachers are no longer simple presenters of knowledge, but active agents, who produce gritty and tough students (Duckworth et al, 2010 ). Grit promotes academic performance, hope, trust, learning motivation, resilience, and success rate (Keegan, 2017 ; Taşpinar & Külekçi, 2018 ; Xu, 2022 ). Furthermore, grit is contended to afford persistent energy, passion, motivation, desire, self-discipline, and self-control for L2 learners (Duckworth & Gross, 2014 ; Li & Yang, 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers are no longer simple presenters of knowledge, but active agents, who produce gritty and tough students (Duckworth et al, 2010 ). Grit promotes academic performance, hope, trust, learning motivation, resilience, and success rate (Keegan, 2017 ; Taşpinar & Külekçi, 2018 ; Xu, 2022 ). Furthermore, grit is contended to afford persistent energy, passion, motivation, desire, self-discipline, and self-control for L2 learners (Duckworth & Gross, 2014 ; Li & Yang, 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning L2 students’ grit, correlational studies reveal that grit predicts well-being, success, satisfaction, willingness to communicate (WTC), achievement, resilience, engagement, and enthusiasm (Fathi et al, 2021 ; Jin & Kim, 2017 ). In a recent study, Xu ( 2022 ) argued that L2 students’ grit is facilitated by teachers’ hope and trust. Furthermore, Wu et al ( 2022 ) identified a positive correlation between grit and EFL students’ performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, they concluded that teacher grit predicted the relationships between EFL teachers’ self-reported pedagogical beliefs and their actual practices. Confirming the scant attention to L2 teacher grit, a theoretical analysis was completed by Xu (2022) , in which the theoretical and empirical literature related to teachers’ hope, trust, and grit were reviewed. Shabani et al (2022) examined to what extend pedagogical thoughts vary as a function of EFL teachers’ levels of grit.…”
Section: Literature Reviewmentioning
confidence: 99%